LIVING WITH ROBOTS: AN ONTOLOGICAL LEAP? - Mays, Kate K.; Lei, Yiming; Katz, James E. (AoIR Selected Papers of Internet Research, 2020)
Artificial intelligence (AI) and robotics applications have proliferated primarily in the industrial sphere, and social scientific studies emphasized robots’ functionality and appropriateness for certain roles, especially those related to work and most particularly to robots replacing humans’ jobs. Notably, robot studies are often premised on negative prognostications, emphasizing how robots threaten livelihoods and are disruptive. As AI and robot technologies advance, however, more positive possibilities arise for robots’ social integration. However, there is an ontological divide between humans and machines that will likely influence people’s responses to and interactions with these emerging technologies. People may logically know and intend to treat robots as mere technological tools, but reflexively respond to them socially. This study explores these possible dynamics and examines how people perceive robots as social and human-like entities. A qualitative analysis of open-ended comments (N=591) collected through a survey on robot perceptions was conducted. Five main themes about social life with robots were revealed: robot as tool/machine (32.5% of comments), human-robot relationships (26.9%), social adjustment (19.0%), robot rights (10.7%), and robots’ aliveness/appearance (10.0%). The findings show that human-robot ontology is an important consideration for robots’ social acceptance and integration. AI-supported robotic technology presents great promise; however, its advancement challenges the ontological divide that has implications not only for human-machine interaction but also for self-identity and ultimately human-human relations. In terms of suggestions, these dynamics should be explored in tandem with ways to improve human-machine communication and considered from usability and design standpoints.